Pooled Unit Root Tests in Panels with a Common Factor - Joakim Westerlund (Lund University, School of Economics and Management, Department of Economics, 2005)
This paper proposes new pooled panel unit root tests that are appropriate when the data exhibit cross-sectional dependence that is generated by a single common factor. Using sequential limit arguments, we show that the tests have a limiting normal distribution that is free of nuisance parameters and that they are unbiased against heterogenous local alternatives. Our Monte Carlo results indicate that the tests perform well in comparison to other popular tests that also presumes a common factor structure for the cross-sectional dependence.
Keywords: C12; C31; C33; 330; Pooled Unit Root Tests; Panel Data; Common Factor; Cross-Sectional Dependence; Monte Carlo Simulation.